2022
DOI: 10.1007/s00203-022-03216-x
|View full text |Cite
|
Sign up to set email alerts
|

The antifungal activity of a serine protease and the enzyme production of characteristics of Bacillus licheniformis TG116

Abstract: The growth of Phytophthora capsica, Rhizoctonia solani, Fusarium graminearum, Fusarium oxysporum and Botrytis cinerea were all inhibited by the fermentation supernatant of Bacillus licheniformis TG116, a biocontrol strain isolated from Typhonium giganteum Engl previously with broad-spectrum resistance to plant pathogens. The fermentation supernatant of the TG116 has a great stability on temperature and UV, and shows the biological activity of serine protease and cellulase. The antifungal protease produced by B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Microbial VOCs have been shown to enhance plant tolerance against both abiotic and biotic stress by activating the SA and JA signaling pathways [ 75 ]. Ling et al [ 76 ] demonstrated the antimicrobial activity of microbial serine proteases. Additionally, serine proteases derived from rhizobacteria have been observed to activate plant immune responses and modify cell wall lignification [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microbial VOCs have been shown to enhance plant tolerance against both abiotic and biotic stress by activating the SA and JA signaling pathways [ 75 ]. Ling et al [ 76 ] demonstrated the antimicrobial activity of microbial serine proteases. Additionally, serine proteases derived from rhizobacteria have been observed to activate plant immune responses and modify cell wall lignification [ 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many antagonistic bacteria secrete hydrolytic enzymes such as chitinase, glucanase, and protease, which plays a major role in fungal suppression ( Fatima et al, 2023 ; Xu et al, 2016 ). For example, the proteolytic activity of antagonistic bacteria exhibits strong inhibitory effect on fungal mycelial growth and conidial germination ( Gandhi Pragash et al, 2009 ; Ji et al, 2020 ; Ling et al, 2022 ). In the current study, a qualitative assay of antagonistic substances showed that the B .…”
Section: Discussionmentioning
confidence: 99%
“…antagonism of phytopathogenic fungi. For instance, the serine proteases (44.3 kDa) from B. licheniformis strain W10 and B. licheniformis strain TG116 demonstrated antifungal activity against B. cinerea [122], and against P. capsica, R. solani, Fusarium sp., and B. cinerea [123], respectively. The protease from B. subtilis strain 21 was effective against F. verticillioides and R. solani in strawberry plants under greenhouse conditions [124], while the protease (31 kDa) from B. licheniformis strain BS-3 was effective against A. niger, M. oryzae, R. solani, and F. oxysporum strains [125].…”
Section: The Prospect Of Proteases From Bacillus Sp As Antifungal And...mentioning
confidence: 98%